The Coordination chemistry of imidomethanedithiolate di-anions: A structural comparison with their dithiocarbamate analogs - Heard, Peter *; Tan, Yee Seng *; Yeo, Chien Ing *; Tiekink, Edward R. T. * (MDPI, 2021)
A review of the coordination chemistry along with the structural features of heavy element complexes of dithiocarbimate di-anions in the form of [(R)C=NCS2]2− for R = CN, alkyl, and aryl are described. This class of compound is far less studied compared with the well-explored dithiocarbamate mono-anions formulated as [R(R’)NCS2]− for R/R’ = H, alkyl, and aryl. The coordination chemistry of dithiocarbimate di-anions is dominated by a S,S-chelating mode; rare examples of alternative modes of coordination are evident. When comparisons are available, the structural motifs adopted by metal dithiocarbimate complexes match those found for their dithiocarbamate analogs, with only small, non-systematic variations in the M–S bond lengths